2006
DOI: 10.1080/0972060x.2006.10643490
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antioxidant Activities of the Essential Oil of Cinnamon (Cinnamomum zeylanicumBlume) Leaves from Sri Lanka

Abstract: The composition of the volatiles from leaves of Cinnamomum zeylanicum Blume from Sri Lanka was studied by GC-FID and GC-MS. The basic component of the oil was found to be eugenol (74.9%), followed by β-caryophyllene (4.1%), benzyl benzoate (3.0%), linalool (2.5%), eugenyl acetate (2.1%) and cinnamyl acetate (1.8%). The essential leaf oil from cinnamon demonstrated scavenger activity against the DPPH radical at concentrations which are lower than the concentrations of eugenol, butylated hydroxytoluene (BHT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 33 publications
4
53
2
1
Order By: Relevance
“…Supplementation of cinnamon oil of both doses to diet reduced MDA production in liver, heart and kidney, especially under HS condition. SCHMIDT et al [36] mentioned about among all oxygen radicals the hydroxyl radical (OH•) was the most reactive and damages diverse biomolecules, and cinnamon oil showed high hydroxyl radical-scavenging activity because of its phenolic structure. FAIX et al [37] observed that 0.1% level C. zeylanicum essential oil significantly decreased the concentration of MDA in plasma and duodenal mucosa, however it had no significant effect on the concentration of MDA in the liver and kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of cinnamon oil of both doses to diet reduced MDA production in liver, heart and kidney, especially under HS condition. SCHMIDT et al [36] mentioned about among all oxygen radicals the hydroxyl radical (OH•) was the most reactive and damages diverse biomolecules, and cinnamon oil showed high hydroxyl radical-scavenging activity because of its phenolic structure. FAIX et al [37] observed that 0.1% level C. zeylanicum essential oil significantly decreased the concentration of MDA in plasma and duodenal mucosa, however it had no significant effect on the concentration of MDA in the liver and kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Sebanyak 1 ml (Anonim, 1988;Burdock et al, 2008). Penelitian sebelumnya memperkuat dugaan ini dimana diketahui bahwa benzil benzoate dapat memerangkap radikal bebas hidroksil, peroksil, dan alkil, sehingga berpotensi sebagai antioksidan (Schmidt et al, 2006;Amalia et al, 2013). Minyak kenanga dengan kandungan antioksidan yang lembut ini dapat digunakan untuk berbagai kegunaan seperti pada campuran bahan kosmetik, obat oles, makanan, minuman, dan lain-lain.…”
Section: Uji Aktivitas Antioksidanunclassified
“…Among them are Cinnamomum sintoc Blume (Indonesia: stem barks 38.8%), C. illicioides A.Chev. (Vietnam: bark 41.2%), C. zeylanicum Blume (Sri Lanka: leaf 74.9%), C. verum J.Presl (Fiji: leaf 86.0%), and C. tamala Nees et Eberm (Bangladesh: leaf 77.3%) (Chowdhury et al, 1981;Giang et al, 2006;Iskandar & Supriyatna, 2008;Schmidt et al, 2006;Patel et al, 2007).…”
Section: Chemical Compositions Of Essential Oilmentioning
confidence: 99%